Digital Competences and Trends in Applications to Support Health Lifestyle - Rahayu, Nur Indri; Muktiarni, M; Ismail, Affero (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
This research aims to analyze trends in researchers' behavior when researching sports applications to support a healthy lifestyle. Bibliometric analysis was used as a method in this research. Research data was collected via the Scopus page starting May 22, 2024. The keywords used were "Sport" AND "Application" "Health" AND "Lifestyle." Search results on the Scopus database found 100 documents from 79 publication sources. The development of article publications regarding sports applications to support a healthy lifestyle can increase yearly. Although, from the highest total publications in 2021, there was a decrease in the number of publications from 2020 to 2024. Fifty-five countries have contributed to publications regarding the use of sports applications to support a healthy lifestyle. The research results show that exercise is most popularly used yearly in research regarding using exercise applications to support a healthy lifestyle. This indicates that researchers use many sports applications as a medium for physical training and training for exercise. Hopefully, this research will become a reference and primary source for further research on using sports applications to support a healthy lifestyle